The Survival of Patients with Triple Negative Breast Cancer Undergoing Chemotherapy Along with Lifestyle Change Interventions: Survival of TNBC patients - Aznab, Mozaffar; Shojae, Shahram; Golpazir Sorkheh, Arash; Eslam pia, Kiumars; Rezaei, Mansour (Archives of Breast Cancer, 2022)
Background: The survival of patients with triple-negative breast cancer subtype undergoing chemotherapy along with weight management, physical activity, and diet was examined. In addition, the relationship between the Overall Survival (OS) of patients with expression P53 and Ki 67 was investigated. Methods: The study was conducted on 110 patients admitted to oncology clinics between October 2009 and July 2018. The patients underwent five chemotherapy cycles, including Docetaxel, Epirubicin, and Cyclophosphamide once every 21 days followed by two cycles of Epirubicin, Cyclophosphamide, and 5-Fluorouracil. The patients also received guidelines for physical exercise, diet, and lifestyle change. Results: The median and mean follow-ups were 52.3 and 45.6 months respectively. Eight patients were metastatic and 103 were under adjuvant therapy, 13 of whom had relapses. The median relapse-free survival and mean OS were 44.4 months and 49.2 months respectively. OS for P53-negative patients was 64.2 months, eight patients relapsed in the P53-positive group, and two relapsed in the P53-negative group. Survival was more favorable in the negative group (P=0.021). The mean DFS in the P53- negative group was 96.1% and 76.3% in the P53-positive group, suggesting a more favorable status in the P53-negative group. Out of 110 patients, 20 died and 90 are still alive. Conclusion: Combining physical exercise, diet, and lifestyle change with chemotherapy increases the chance of a better response to treatment and a reduction in the rate of relapse during the first three years. The survival rate was better in p53-negative patients.